IMPLEMENTASI DAN ANALISIS OPTIMASI BANDWIDTH DENGAN QUEUE TREE MENGGUNAKAN ALGORITMA HTB STUDI KASUS: PT. SUMBER KREASI FUMIKO - Taufik Rahman (LPPM Universitas Bina Sarana Informatika, 2012)
Queue Tree is one of the Bandwidth management becomes essential for multi-service networks, more and varied applications that can be served by a network effect on the use of links in the network. The links that exist should be able to handle the needs of the application client will tesebut even though in a state of congestion, there must be a guarantee that the link still works properly despite an explosion in demand for application. Bandwidth management has animPortant role in the distribution of quotas for these types of applications that can access the link, in addition to Bandwidth management to provide better Bandwidth guarantees to applications that have been allocated Bandwidth to continuously transmit data in accordance with the allocation though there is congestion in the network or the client even in Under certain circumstances when the Bandwidth allocation that is owned by an application or client is not used, then the Bandwidth Manager idle Bandwidth can be temporarily transferred to the classroom who are experiencing Queues, this gives the advantage of a class Queue accelerating loss while optimizing the use ofexisting links. Hierarchical Token Bucket (HTB) as the implementer of the available bandwidth management can be run on linux operating system platform is also available on Mikrotik Router which are Queue HTB tree is proper bandwidth management analysis, is expected to use a precise and accurate will make the network work optimally.Keywords: Bandwidth, HTB, Queue Tree.